2014
DOI: 10.2141/jpsa.0120136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phytase Transgenic Corn on Growth Performance and Calcium and Phosphorus Utilization in Broilers

Abstract: The goal of this study was to determine the effects of phytase transgenic corn (PTC) in low phosphorus (P) cornsoybean meal diets on growth performance, and P and calcium (Ca) utilization by broilers. Six hundred and forty 1-day-old male broiler chicks were randomly divided into four groups, with eight replicates of 20 birds in each group, and fed for 42 days. Four treatments consisted of a positive control (PC), a negative control (NC), a PTC group and an exogenous phytase (EP) group. The PC group was fed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It has been reported that PTC (containing phytase activity of 12,000 FTU/kg of DM) could maintain 86.6% of the original phytase activity when it was heated in an oven at a temperature of 120°C and 12.5% when the PTC-based diet (containing phytase activity of 7480 FTU/kg of DM) was pelleted at a temperature of 60°C (Wu, 2010). Therefore, as an innovative way of delivering microbial phytase to monogastric animals for better utilization of phytate-bound P, PTC will remove the need for extra phytase to be added to animal diets, therefore lowering feed production costs.…”
Section: Phosphorus Digestibilitymentioning
confidence: 99%
“…It has been reported that PTC (containing phytase activity of 12,000 FTU/kg of DM) could maintain 86.6% of the original phytase activity when it was heated in an oven at a temperature of 120°C and 12.5% when the PTC-based diet (containing phytase activity of 7480 FTU/kg of DM) was pelleted at a temperature of 60°C (Wu, 2010). Therefore, as an innovative way of delivering microbial phytase to monogastric animals for better utilization of phytate-bound P, PTC will remove the need for extra phytase to be added to animal diets, therefore lowering feed production costs.…”
Section: Phosphorus Digestibilitymentioning
confidence: 99%